Disruptive Innovations for Well-Functioning Food Systems: The Data-Driven “Food and Nutrition Security Under Climate Evolution” Framework - Pacillo, Grazia; Bao-Nam, Nguyen-Vu; Burra, Dharani Dhar; Trinh, Huong T.; Le, Tuyen Danh; Truong, Mai Tuyet; Nguyen, Son Duy; Tran, Do Thanh; Läderach, Peter (Frontiers in Sustainable Food Systems, 2022)
The current climate crisis poses new uncertainties, risks, and vulnerabilities, and is leading to losses for millions of people depending on fragile food systems. Food systems are, however, vastly different across landscapes and communities, and their capacities to respond to climate impacts evolves and changes through time. Humanitarian and development organisations are struggling to keep pace with these changes. Monitoring a large number of diverse food systems during an evolving climate crisis can be expensive and time-consuming. This paper introduces a monitoring approach that uses a combination of open-source earth observations along with national data sources to produce highly contextualised metrics for monitoring Food And Nutrition Security under Climate Evolution (FANSCE). Entirely data-driven, the FANSCE approach has been designed to produce policy recommendations to help monitor, assess, and mitigate climatic impacts on food systems. We developed and tested this approach in Vietnam, where climate variability has become a growing threat to food systems. Our results show that predictors of food and nutrition security differ drastically with the intensity of climate variability. More specifically, our analyses suggest that in areas of high climate variability, levels of food and nutrition security can be significantly predicted based on economic activities, ethnicity, education, health of mothers, and the level of readiness and preparedness to climate impacts of villages and communities. On the other hand, in areas of low climate variability, food and nutrition security are mostly predictable based on the ability of households to access essential services (such as education, health) and communal resources (water, storage, etc.). To support the resilience of food systems, policymakers must regularly monitor how these dimensions react to the changing climate. Addition critical actions to increase food system sustainability in Vietnam include 1) enhanced coordination of institutional responses and capacities across governmental and non-governmental agencies, and 2) better integration of scientific knowledge into national and sub-national decision-making processes.